Penerapan Standar Pelaporan Keberlanjutan GRI dan Profitabilitas terhadap Nilai Perusahaan - Victoria Ari Palma Akadiati; Agnes Susana Merry Purwati; Imelda Sinaga (Universitas Batanghari Jambi, 2023)
This study was conducted with the aim of examining the effect of the implementation of Global Reporting Initiative (GRI) sustainability reporting standards and profitability on the value of companies listed on the stock exchange market on the Indonesia Stock Exchange. The sample was selected using purposive sampling method with multiple linear regression research model. The results obtained from this study can provide additional literacy for other researchers because based on data analysis, it can be concluded that neither the Global Reporting Initiative Standard (GRI Standard) nor profitability have a significant effect on the value of the companies that are the research sample. The implementation of the GRI Standard is expected to provide information on economic, environmental, and social impacts to improve reputation, build trust, and improve risk management which is currently presented separately from financial reporting, namely a separate sustainability report and is still voluntary disclosure.